Effective learning interaction as a prerequisite to successful Open Distance Learning (ODL): A case study of learners in the northern state of Kedah and Perlis, Malaysia - Dzakiria, Hisham; Kasim, Azilah; Mohamed, Abdul Halim; Christopher, Anne Althea (Anadolu University, 2013)
The provision of ODL is now largely available in most part of the world, and is just a matter of choice for working adults to pursue. With the competing priorities of work, home, and school, adult learners everywhere desire a high degree of flexibility and accessibility.The structure of ODL provides learners with the greatest flexibility. It provides control over time, place and pace of education; however, learning at a distance is not without problems. Loss of student motivation due to lack of face-to-face (f2f) contact with tutors, peers and content; high startup costs, and lack of support are all barriers to the success of ODL. One important element of success factor for students attending ODL program is the level of interactivity within the student-tutor-content dyads.This paper looks at the issue of interactivity as reported in this research on students’ perspectives and experiences of ODL programs in the northern part of Malaysia. The study supported the widely held belief that a high level of interaction is desirable in ODL environment (Dzakiria, 2008, Dzakiria & Idrus, 2003; Rumble, 2000; Walker, 2002)) and positively affects the learning experiences.Recent technological advancements, allowing an increasing level of interaction between the interactivity dyads have implicated how teaching and learning should be in an ODL environment.This study believes to improve ODL experience, decrease dropout rates and maintain success stories for ODL, tutors and all-important stakeholders in ODL must improve the provision of interaction and interactivity.It is evident from the literature that there is a still research gap on interaction issues in ODL which must be pursued and address to improve the learners’ educational experience-for they are the primary clientele of ODL.